1996
DOI: 10.1007/s002849900043
|View full text |Cite
|
Sign up to set email alerts
|

Diarrheal and Environmental Isolates of Aeromonas spp. Produce a Toxin Similar to Shiga-Like Toxin 1

Abstract: Diarrheal and environmental isolates of 39 strains of Aeromonas spp. were studied for detection of virulence factors. Although these 39 strains did not produce either heat-labile or heat-stable enterotoxins, culture filtrates of 31 strains produced cytopathic effects on Vero cells. Among these, culture filtrates of three strains of Aeromonas hydrophila and one strain of Aeromonas caviae could be neutralized by Escherichia coli O157:H7 Shiga-like toxin 1 antiserum. A single band of plasmid DNA of 2.14 kbp was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 38 publications
0
31
1
Order By: Relevance
“…There are many reports of bacteria that can produce Stx, although not all species are normally associated with toxin production (7,20,23,30,37). The production of Stx-like toxins in strains of C. freundii and Aeromonas spp., for example, may be due to bacteriophage-mediated transfer of vt genes from the STEC reservoir.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports of bacteria that can produce Stx, although not all species are normally associated with toxin production (7,20,23,30,37). The production of Stx-like toxins in strains of C. freundii and Aeromonas spp., for example, may be due to bacteriophage-mediated transfer of vt genes from the STEC reservoir.…”
Section: Discussionmentioning
confidence: 99%
“…Genes encoding Stx are most typically associated with Shigella dystenteriae and E. coli O157:H7, but they have been found in E. coli strains encompassing Ͼ100 serotypes, as well as other species of gram-negative bacteria, including Citrobacter freundii (30,37), Vibrio cholerae (20), Enterobacter cloacae (23), and Aeromonas spp. (7).…”
mentioning
confidence: 99%
“…hydrophila infection (Bogdanovic et al 1991;Janda and Kokka 1991;Robson et al 1992) and a cytotoxin with homology to Shiga toxin 1 has been identified in both the A . hydrophila and A. caviae (Haque et al 1996). According to Kirov (2001), the majority of aeromonads associated with gastroenteritis belong to A .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Poirier et al (35) reported a case of pneumonia of nosocomial origin caused by A. hydrophila that complicated toxic coma, while both A. hydrophila and A. sobria have been isolated from humans with sepsis, peritonitis, urinary tract infections, and severe muscle degeneration (12). Hemolytic-uremic syndrome, a life-threatening condition normally associated with infections due to Escherichia coli O157: H7, has also been associated with A. hydrophila infection (6,23,37); and a cytotoxin with homology to Shiga toxin 1 has been identified in both A. hydrophila and A. caviae (18).…”
mentioning
confidence: 99%